Improving Grade 11 Students’ Reading Comprehension Skills through Focused Tasks at A High School in Nam Dinh = Nâng cao kỹ năng đọc hiểu cho học sinh lớp 11 tai một trường trung học phổ thông ở Nam Định qua các bài tập trọng điểm. M.A Thes - Trần, Thị Thanh Hòa, 1981- (University of Languages and International Studies, 2017)
In many second or foreign language teaching situations, reading receives a special focus. In process of teaching and learning English as a foreign language, reading has always been offered a great deal of attention both from the teachers and the students. Reading is not only considered as a means to gain knowledge but also a means by which further study takes place. This study is concerned with improving students’ reading comprehension skills through focused tasks. The benefits of using focused tasksin reading lessons are affirmed again in this thesis through the studies and the researcher carried out atNgo Quyen High School, Nam Dinh province. These benefits bring considerable effectiveness to teachers and students in teaching and learning reading. This is also the main aim of the study and the researcher’s wish.In order to achieve this aim and wish, the researcher enters into consideration of the relevant literature and then carries out observing classes, giving questionnaires to them, etc. to have necessary findings and analysis. At the same time, the researcher also suggests the suitable reading tasks to apply in teaching and learningreading lessons in Tieng Anh 11.